Forward-Thinking And Its Relationship with Decision-Making Skills of The Middle School Mathematics Teachers - Prof. Asaad Kadim Mohammed, Asst. Prof. Dr. Basim Mohammed Jassim (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current study aimed to recognize the relationship between Forward-thinking and Decision-making skills of the middle school mathematics teachers. The researcher adopted the descriptive-correlational approach. The research community consisted of middle school mathematics female and male teachers affiliated with the Education Directorate of Babylon. The research sample consisted of(60) female and male teachers,(25) male teachers, and (35) female teachers who are specialists in middle school mathematics and affiliated with the middle schools of the Education Directorate of Babylon. The researcher designed the study tools to collect the data of the study, which was a Forward-thinking test consisted of (20) items, (11) essay type, and (9) topical type, as well as a Decision-making skills test consisted of (18) items, (14) essay, and (4) topical. The researcher made the appropriate statistical analyses to the two test items and their psychometric properties were verified. After using the statistical tools in analyzing the results of applying the two tests, the findings were as follow: The sample individuals have an acceptable range of Forward-thinking. The sample individuals have an acceptable range of Decision-making skills. There is a strong relationship between Forward-thinking and Decision-making skills. The researcher introduced some recommendations and suggestions for those concerned in the field of research and education according to the research results.